CAFÉ: a multicomponent audit and feedback intervention to improve implementation of healthy food policy in primary school canteens: protocol of a randomised controlled trial. Issue 6 (24th June 2015) - Williams, Christopher M; Nathan, Nicole; Delaney, Tessa; Yoong, Sze Lin; Wiggers, John; Preece, Sarah; Lubans, Nicole; Sutherland, Rachel; Pinfold, Jessica; Smith, Kay; Small, Tameka; Reilly, Kathryn L; et al.
Abstract : Introduction: A number of jurisdictions internationally have policies requiring schools to implement healthy canteens. However, many schools have not implemented such policies. One reason for this is that current support interventions cannot feasibly be delivered to large numbers of schools. A promising solution to support population-wide implementation of healthy canteen practices is audit and feedback. The effectiveness of this strategy has, however, not previously been assessed in school canteens. This study aims to assess the effectiveness and cost-effectiveness of an audit and feedback intervention, delivered by telephone and email, in increasing the number of school canteens that have menus complying with a government healthy-canteen policy. Methods and analysis: Seventy-two schools, across the Hunter New England Local Health District in New South Wales Australia, will be randomised to receive the multicomponent audit and feedback implementation intervention or usual support. The intervention will consist of between two and four canteen menu audits over 12 months. Each menu audit will be followed by two modes of feedback: a written feedback report and a verbal feedback/support via telephone. Primary outcomes, assessed by dieticians blind to group status and as recommended by the Fresh Tastes @ School policy, are: (1) the proportion of schools with a canteen menu containing foods or beverages restricted for sale, and; (2) the proportion of schools that have a menu which contains more than 50% of foods classified as healthy canteen items. Secondary outcomes are: the proportion of menu items in each category ('red', 'amber' and 'green'), canteen profitability and cost-effectiveness. Ethics and dissemination: Ethical approval has been obtained by from the Hunter New England Human Research Ethics Committee and the University of Newcastle Human Research Ethics Committee. The findings will be disseminated in usual forums, including peer-reviewed publication and conference presentations. Trial registration number: ACTRN12613000543785.